Analisis Pengaruh Tren Budaya, Brand Ambassador dan Harga terhadap Purchase Intention - Francisca Triyana Resti Prastiwi; Christina Sri Ratnaningsih; Irany Windhyastiti; Umu Khouroh; Irany Windhyastiti (Jurnal Bisnis dan Manajemen, 2020)
This research aims to find out how the influence of cultural trends, brand ambassadors and prices on the purchase intention of Korean instant noodles. The population in this study is Twitter users, members of Korean Pop fans who idolize the ambassador brand from the Korean band "Super Junior" who consume instant noodles. The number of samples taken in this study used the Lemeshow formula as much 100 respondents. The sampling technique uses non-probability techniques, namely incidental sampling techniques. The analytical tool used in this study is Multiple Regression Analysis. The results show that: 1) the culture trend of Korean Wave variable does not have a significant effect on purchase intention, 2) the brand ambassador variable  has a significant effect on purchase intention, and 3) the price variable has a significant effect on purchase intention